Radiation Exposure Assessment in Coronary Angiography Computed Tomography Scan: Establishing Diagnostic Reference Level for Northeast Assam Population - Sarma, Arnabjyoti Deva; Sharma, Jibon; Sarma, Manash Pratim; Singha, Mrinal Kanti (Scripta Medica, 2024)
Background/Aim: Coronary angiography computed tomography (CT) scans play a pivotal role in diagnosing cardiovascular diseases, providing crucial information for treatment planning. However, concerns regarding radiation exposure have prompted the need for establishing region-specific diagnostic reference levels (DRLs) to ensure patient safety. This study aimed to assess radiation exposure during coronary angiography CT scans in the northeast Assam population and establish DRLs tailored to this demographic. Methods: A total of 380 patients were referred to the Primus Diagnostic Centre and Heath City Hospital, Guwahati Assam with coronary artery disturbances. Data on the technical parameters used in CT procedures were taken in 2021-2022. Organ and surface dose to specific radiosensitive organs (chest) estimation was done using software imPACT 1.0.4 from the National Radiological Protection Board (NRPB) SR250 Monte Carlo dataset. Results: The study population (n = 380) comprised 190 men and 190 women with an age range from 29 to 75 years. The mean body mass index (BMI) and effective dose (ED) were 22.42 ± 1.06 kg/m2 and 21.57 ± 4.27 mSv.cm, respectively. The mean the dose-length product (DLP) was 854.67 mSv.cm and the mean ED was 21.57 mSv.cm. The ED for males was 13- 27 mSv and 13-29 mSv for females. The DRL for the male population was found to be 24.26 mSv.cm2 whereas for the female population was 24.69 mSv.cm2. Conclusion: This study highlights the necessity of establishing tailored DRLs for coronary angiography CT scans in the northeast Assam population. By doing so, healthcare providers can ensure optimal image quality while minimising radiation exposure, ultimately enhancing patient safety and quality of care. These findings have implications for radiological practice in the region and contribute to the ongoing efforts to standardise radiation doses in medical imaging procedures.